ANALISA OVER CURRENT RELAY (OCR) PADA TRANSFORMATOR DAYA 60 MVA DENGAN SIMULASI MATLAB DI GARDU INDUK PAYA GELI - Anisah, Siti; Wardani, Dwi Putri; Rahmaniar, Rahmaniar; Hamdani, Hamdani (Scenario (Seminar of Social Sciences Engineering and Humaniora), 2021)
The distribution of electrical energy properly many aspects that need to be considered is the reliability of the protection system. To maintain the reliability of electrical equipment, especially transformers, a protection system is needed. A protection system is a system that functions to prevent or limit damage to equipment as a result of interference. One type of protection used is Over Current Relay (OCR). Where the working principle of the OCR is to detect the presence of overcurrent that exceeds the predetermined setting value, whether caused by a short circuit between phases or overload. In this paper, describes the use of the electric circuit method. The simulation of this electric circuit method uses Matlab as a verification calculation. The results of the calculation of the inter-phase fault current that occur, the largest value of short circuit fault currents between phases is located at 0% point of 8113.79 Ampere and the smallest value of short circuit fault currents between phases is at 100% point of 1208.10 Ampere and comparison with experiments using the matlab application obtained results that are not too far from the results of manual calculations